Comparative analysis of net and gross-up methods in PPh 21 calculation as a tax planning strategy - Novita Djuliani; Mahwiyah Mahwiyah (Priviet Social Sciences Journal, 2026)
This study examines the application of tax planning through net and gross-up methods to determine employee income tax within an educational foundation. Using a descriptive quantitative approach, this study analyzes payroll components, employee benefits, and the treatment of tax obligations under both methods. The findings indicate that the net method provides administrative simplicity but reduces employees’ take-home pay, whereas the gross-up method increases employee welfare by allowing the institution to bear the tax burden as a deductible expense for the institution. The comparison highlights that the gross-up method offers a stronger alignment with organizational objectives related to transparency, compliance, and financial efficiency. This study contributes to a deeper understanding of tax planning strategies in nonprofit entities and provides practical insights for institutions seeking to optimize their compensation structures while maintaining adherence to prevailing regulations.